Identification of F1 hybrids of poinsettia by RAPDS - Barragán-Martínez, Juan Antonio; Rodrìguez Rojas, Teresa de Jesùs; Andrade-Rodríguez, María; Villegas-Torres, Oscar Gabriel (Revista Mexicana de Ciencias Agrícolas, 2021)
Mexico is the center of origin of poinsettia Euphorbia pulcherrima Willd. ex Klotzsch, it is native to the state of Morelos. The molecular identification of hybrids determines the phylogenetic relationships between them. The objective of the present research was to identify F1 hybrids of E. pulcherrima using RAPD molecular markers. Thirty-nine F1 plants from the crosses of three varieties of sun poinsettias (Amanecer navideño, Belén and Juan Pablo) with three shade varieties (Festival red, Ice Punch and Burgundy) were used. Clustering analyses were performed on the relationship of matrices with the linkage method of unweighted pair groups with arithmetic mean (UPGMA). The OPA-07 primer is the one that allowed identifying the hybrid origin of 7 F1 plants of the Juan Pablo x Ice Punch cross. From the progeny of the crosses of Amanecer navideño x Ice Punch and Amanecer navideño x Festival red, the OPA primer identified 8 plants as hybrids. The RAPD primers used in the crosses obtained from Belén x Ice Punch, Belén x Burgundy and Belén x Festival red, failed to identify the parents with the hybrid progeny, the fragments did not show differences even between the same parents.